1995
DOI: 10.1111/j.1751-1097.1995.tb02412.x
|View full text |Cite
|
Sign up to set email alerts
|

PHOTOMORPHOGENIC RESPONSES TO UV RADIATION III: A COMPARATIVE STUDY OF UVB EFFECTS ON ANTHOCYANIN and FLAVONOID ACCUMULATION IN WILD‐TYPE and aurea MUTANT OF TOMATO (Lycopersicon esculentum MILL.)

Abstract: The UV‐mediated induction of anthocyanin and UV‐absorbing compounds was characterized in etiolated hypocotyls of wild‐type and aurea (au) mutant tomato seedlings. Ultraviolet radiation induced significant increases of anthocyanin and UV‐absorbing compounds in hypocotyls of die au mutant and of its isogenic wild‐type, but the differences in the time courses of UV‐induced pigment accumulation indicate mat different photoregulatory mechanisms are involved for each of these two groups of pigments. It appears mat p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
20
0
1

Year Published

2006
2006
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(24 citation statements)
references
References 26 publications
3
20
0
1
Order By: Relevance
“…Therefore, accumulation of anthocyanin and/or flavonoids in response to UV-B radiation is an adaptive defence mechanism, and their accumulation has been used as a marker of adaptation in our work. UV-B induced enhancement in the contents of flavonoids and anthocyanin in primary leaves of wheat seedlings is in conformity with earlier works (Lindoo and Caldwell 1978, Beggs and Wellmann 1994, Brandt et al 1995, Olsson et al 1998, Gao et al 2004). Accumulation of UV-absorbing substance throughout the leaf development of spinach seedlings has been observed by Hada et al (2001).…”
Section: Discussionsupporting
confidence: 88%
“…Therefore, accumulation of anthocyanin and/or flavonoids in response to UV-B radiation is an adaptive defence mechanism, and their accumulation has been used as a marker of adaptation in our work. UV-B induced enhancement in the contents of flavonoids and anthocyanin in primary leaves of wheat seedlings is in conformity with earlier works (Lindoo and Caldwell 1978, Beggs and Wellmann 1994, Brandt et al 1995, Olsson et al 1998, Gao et al 2004). Accumulation of UV-absorbing substance throughout the leaf development of spinach seedlings has been observed by Hada et al (2001).…”
Section: Discussionsupporting
confidence: 88%
“…Leaf anthocyanin levels often increase in response to UV-B radiation in laboratory trials (Alexieva et al, 2001;Brandt et al, 1995;Lindoo and Caldwell, 1978) and their presence can alleviate DNA damage (Kootstra, 1994;Li et al, 1993). Under field conditions, with balanced UV-A/visible radiation, mildly enhanced UV-B radiation may (Mendez et al, 1999) or may not (Dillenburg et al, 1995) result in increased anthocyanin levels.…”
Section: Anthocyanins May Not Be An Effective Uv-b Screenmentioning
confidence: 97%
“…As regards phenolic compounds, although genetic control represents the main factor in determining their accumulation in vegetable foods, external factors may also have a significant effect on this (Macheix et al, 1990). In many plant species the flavonol content may be enhanced in response to elevated light levels, in particular to increased UV-B radiation (Brandt et al, 1995). As a matter of fact, it has been reported that cherry tomato plants grown in greenhouse under high light accumulated an approximately two-fold greater soluble phenols content (rutin and chlorogenic acid) than low-light plants (Wilkens et al, 1996).…”
Section: Introductionmentioning
confidence: 98%